IMPACT OF WATER IMPURITIES ON DRILLING FLUID PROPERTIES: A CASE STUDY - Amel Habeeb Assi (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
As diagnosed, water is an essential component in the preparation of water base mud, but drilling fluids cannot be prepared with high-purity water (practically and economically unavailable), as water may sometimes contain salts and ions such as chlorides and sulfates, negatively affecting the quality and properties of the mud. This research aims to find the effect of impure water on the drilling fluid and then provide the necessary solutions and treatments for that. Samples of water were used and examined, and they contained a percentage of calcium ions at a rate of 800gm/liter, 1000 gm/liter, and 1400 gm./liter, this is unacceptable, so soda ash was used to reduce the above percentages. On the other hand, the water samples had a salinity of 20,000, 30,000, and 40,000 ppm/liter, which is undesirable, so it is preferable to dilute the mud by adding water. The results showed the effect of the presence of those salts on the effectiveness of the added polymers, as well as causing problems with CMC, as it reduces its performance in increasing the viscosity of the mud. The results showed that the acceptable percentage of calcium should be less than 400 mg/liter, and salinity should not exceed 10000 ppm/liter. The results also proved the negative effect of the presence of sulfate in the water on the properties of the drilling fluid, as it reduced its viscosity and pH. This was treated by adding caustic soda to the drilling mud to increase the pH. It was also noted that the addition of caustic soda led to an increase in the viscosity of the drilling mud. What is novel in this research is that it is possible to treat contaminated drilling mud by adding environmentally friendly materials such as micro-silica to reduce the effect of contamination with calcium ions.